Response-To-Intervention in Finland and the United States: Mathematics Learning Support as an Example - Björn, Piia M.; Aro, Mikko; Koponen, Tuire; Fuchs, Lynn S.; Fuchs, Douglas (Frontiers in Psychology, 2018)
Response to Intervention (RTI) was accepted in the early 2000s as a new framework for identifying learning difficulties (LD) in the U.S. In Finland, a similar multi-tiered framework has existed since 2010. In the present study, these frameworks are presented from the viewpoint of the role of assessment and instruction as expressed in documents that describe the frameworks, as it seems that these two components of RTI are the most disparate between the U.S. and Finland. We present a suggestion for the Finnish framework as an example of support in mathematics learning that, incorporates principles of RTI (such as systematized assessment and instruction, cyclic support, and modifiable instruction). Finally, recommendations are presented for further refining and developing assessment and instruction policies in the two countries. Key words: Response to Intervention framework; Assessment; Instruction; Support in Mathematics